2020
DOI: 10.1093/mnras/staa1742
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the radio continuum nature of sources in the massive star-forming region W75N (B)

Abstract: ABSTRACT The massive star-forming region W75N (B) is thought to host a cluster of massive protostars (VLA 1, VLA 2, and VLA 3) undergoing different evolutionary stages. In this work, we present radio continuum data with the highest sensitivity and angular resolution obtained to date in this region, using the VLA-A and covering a wide range of frequencies (4–48 GHz), which allowed us to study the morphology and the nature of the emission of the different radio con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…Shepherd 2001;Minh et al 2010). Three radio continuum sources were also detected towards MM1 (VLA1, VLA2 and VLA3), which have been identified as ultra-compact HII (UC HII) regions or thermal jets (Hunter et al 1994;Torrelles et al 1997;Shepherd et al 2003;Carrasco-González et al 2010;Rodríguez-Kamenetzky et al 2020). Shepherd et al (2004) found that the VLA sources drive high-velocity molecular outflows traced by SiO (2−1 and 1−0) emission.…”
Section: Introductionmentioning
confidence: 99%
“…Shepherd 2001;Minh et al 2010). Three radio continuum sources were also detected towards MM1 (VLA1, VLA2 and VLA3), which have been identified as ultra-compact HII (UC HII) regions or thermal jets (Hunter et al 1994;Torrelles et al 1997;Shepherd et al 2003;Carrasco-González et al 2010;Rodríguez-Kamenetzky et al 2020). Shepherd et al (2004) found that the VLA sources drive high-velocity molecular outflows traced by SiO (2−1 and 1−0) emission.…”
Section: Introductionmentioning
confidence: 99%
“…G345.49+1.47 is part of a small group of HMYSOs toward which active disk accretion has been proposed while simultaneously exciting an Hii region. Other like sources are G35.20−0.74N and recently W75N (B) VLA1 (Rodríguez-Kamenetzky et al 2020). G345.49+1.47 was also part of the sources studied by Cesaroni et al (2017) at 0.…”
mentioning
confidence: 84%
“…The radio sources are unresolved in the map. Also, 1112-r4 and r5 are likely to be one radio HH-object (Rodríguez-Kamenetzky et al 2020).…”
Section: Radio Flux Densitymentioning
confidence: 99%
“…Only nine sources meet the criteria of UC-or HC-H II regions in at least one map. Two of them are the most luminous radio sources in MDC 1112, whose natures have been long under debate (Torrelles et al 1997;Shepherd 2001;Carrasco-González et al 2010b;Rodríguez-Kamenetzky et al 2020). Source 675-r1 reaches the criteria only on the Q-band A-configuration map, which only picks up the most compact components.…”
Section: H II Regionsmentioning
confidence: 99%
See 1 more Smart Citation